The effect of workload on organizational citizenship behaviour (OCB) with work motivation in Islamic perspective as a mediating variable - Sutrisno Sutrisno; Mutiara Indriasari (Al Tijarah, 2020)
This research aims at identifying the impact of workload toward Organizational Citizenship Behavior (OCB) and the mediating role of work motivation in Islamic perspective on the impact of workload toward OCB. This research was conducted at BPRS Madina Sejahtera Yogyakarta. Sample used in the research were in total of 31 respondents which were compiled through saturated sampling technique. Data compiling were done through questionnaire and interview. The analysis tool used was SmartPLS 3.2 of outer model and inner model. The research result showed that workload had directly given a positive and significant impact toward OCB; which indicated that the increase of employees’ workload is in line with the increase of employees’ OCB. Besides, work motivation in Islamic perspective had been serving as the competitive partial mediation which indicated that Islamic work motivation had partially mediated the impact of workload toward OCB.